Implementasi Murabahah Pada Perbankan Syariah - Diah, Muhammad; Zulhamdi, Zulhamdi (Al-Hiwalah: Journal of Sharia Economic Law, 2022)
Murabahah is a form of buying and selling goods developed by Islamic banking. In Islamic banking, murabahah dominates the bank's income from the products available in all Islamic banks. Murabahah also provides many benefits to Islamic banks/Islamic banks, one of which is the profit that arises from the difference between the purchase price from the seller and the selling price to the customer. Murabahah as an exchange transaction contract requires the seller to have the right to take legal action against the object he sells. In addition, murabahah as a form of trust buying and selling requires the seller and the buyer to know each other and be honest with each other regarding the object of sale, both the specifications of the goods, the acquisition price, the desired margin, and the method of payment. Included in the acquisition price is the cost of goods and their procurement costs until the acquisition price is only known after the goods are legally owned by the seller. Along with the emergence and development of the Islamic banking industry, murabahah was adopted as one of the contracts in Islamic bank financing products.